Analysis of structure and content of studying and training process of hurdlers during the preparing process of year cycle - Victoriia Turliuk (Kazimierz Wielki University, 2017)
Relevance. This article deals with issues of periodization of studying and training process of hurdlers during the preparing process of year cycle. Research tasks concern gradual reaching the aim and description of peculiarities of programming hurdlers' year cycle according to the total volume of load during the mezocycle of preparing period. It has been analyzed peculiarities of constructing double preparing cycle according to specific physical qualities which hurdlers possess. It was determined peculiarities of following to the principle of progress (similar to the waves) as well as dynamic of load in basic mezocycle of preparing period during to the year cycle of preparation. Conclusion. It has been determined according to the literature resources that such factors as rational approach of different directions, ways of sport training during preparing period of year cycle give possibility for sportswomen achieve appropriate sport form. As a result of pedagogical research it was determined the structure and content of preparing period of year mezocycle. Appropriate planning of ways of training, as well as training loads of different directions, means of (PT, SPT, TT) as for designed structure of microcycles gives chance to encourage process of hurdlers' preparing. Further researches will be connected with studying of structure and content of training process of hurdlers during of different cycles of preparation.